Codex as a legislative act: linguistic and legal analysis of the criminal codex of ukraine as of August 4, 2025 - Pyatetska, Olga (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article is devoted to linguistic and legal analysis of the current Criminal Codex of Ukraine as of August 4, 2025. The study wa scarried out on the basis of observations of the Criminal Codex of Ukraine as of August 4, 2025. The tendency to integrate knowledge from various related fields is traced, which led to the emergence of new interdisciplinary sciences, include juristiclinguistics. It focuses on the study of communicative resource and stylistic potential of the language of law, high-quality linguistic support for law making, law enforcement, the correct use and interpretation of legal terms, as well as the implementation of linguistic expertise of oral and written texts, in particular those of a conflict and pathogenic nature. Based on the material of the aforenamed criminal codex, analysis of structural, content and linguistic-stylistic features was carried out, which is relevant in modern research legal-linguistic space. The importance of improving the quality of regulatory and legal documents for the effective regulation of legal relations and the proper functioning of Ukrainian legislation is emphasized. Substantive and procedural codexes are distinguished and characterized, depending on the type of legal norms contained in the codex. The division was made despite the existence of different criteria for classifying codexes. The possibility of codexes changing over a certain period of time after their adoption was emphasized, despite their inherentimmut abilit and so-called external stability - existence over a long period of time, and internal stability – related to the content of the norms contained in the codexes. The main reasons for the variability of codexes are named: political, social, economic, legal, etc. The need to make changes to the current codexes is justified. The structural and substantive changes in the new edition of the Criminal Codex of Ukraine as of August 4, 2025 are considered in detail: supplementing articles with new parts, replacing terms, updating the conceptual and terminological apparatus, etc.